2004
DOI: 10.1111/j.1365-2621.2004.tb06349.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Nisin from Methylcellulose-Hydroxypropyl Methylcellulose Film Formed on Low-density Polyethylene Film

Abstract: Low-density polyethylene film was coated with a solution containing a high-molecular-weight or low-molecular-weight methylcellulose and hydroxypropyl methylcellulose. Films contained 10000, 7500, 5000, 2500, or 0 IU/cm 2 nisin. Film samples were placed into peptone water, and 10-L samples were removed and placed onto spiral plated lawns of Listeria monocytogenes. Zones of inhibition were measured using a caliper. Films containing 5000, 7500, and 10000 IU/cm 2 nisin inhibited L. monocytogenes after 30 min; film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 15 publications
(10 reference statements)
2
14
0
Order By: Relevance
“…2); subsequent pathogen growth after 21 and 28 days indicates that the bacterium developed resistance to the action of nisin over time. This is in agreement with the study by Grower et al (2004), who reported that for maximum effectiveness of nisin films against L. monocytogenes, the nisin should be released and remain effective for the full time period, since any period without release may allow the pathogen to grow and become resistant. These authors used nisin concentrations up to 10,000 IU/g, the maximum level allowed by the FDA for foods.…”
Section: Inhibition Of L Monocytogenes On Salmon Covered With Alginasupporting
confidence: 89%
“…2); subsequent pathogen growth after 21 and 28 days indicates that the bacterium developed resistance to the action of nisin over time. This is in agreement with the study by Grower et al (2004), who reported that for maximum effectiveness of nisin films against L. monocytogenes, the nisin should be released and remain effective for the full time period, since any period without release may allow the pathogen to grow and become resistant. These authors used nisin concentrations up to 10,000 IU/g, the maximum level allowed by the FDA for foods.…”
Section: Inhibition Of L Monocytogenes On Salmon Covered With Alginasupporting
confidence: 89%
“…The possibility of adherence of HPMC and PE films was obtained by PE film corona surface treatment at a potency of 5 kW before coating. Similarly, Grower, Cooksey, and Getty (2004) reported that nisin addition made no difference in the mechanical properties of LDPE films coated with a nisin-containing cellulose-based coating.…”
Section: Mechanical Propertiesmentioning
confidence: 94%
“…The diffusion of potassium sorbate was studied by analyzing its concentration from the other chamber. In several studies involving commonly used synthetic films, the method of incorporation of the antimicrobial substance has been by coating the film with a solution containing the antimicrobial [7,19], while in others it has been possible to incorporate directly the substance in the film matrix [1,2,35]. This suggests that it is not always possible to incorporate the studied antimicrobial directly in the films' matrix.…”
Section: Diffusion Of Antimicrobials Through Food-packaging Polymersmentioning
confidence: 97%